2020
DOI: 10.1002/ijfe.2176
|View full text |Cite
|
Sign up to set email alerts
|

The news effects on exchange rate returns and volatility: Evidence from Pakistan

Abstract: This article explores the effects of macroeconomic news on Pak rupee's exchange rates. For this purpose, it employs GARCH models by using realtime data on macroeconomic news and exchange rates. The results exhibit that daily Pak rupee exchange rates dynamics are linked to macroeconomic fundamentals. Both foreign and domestic macroeconomic news announcements significantly affect Pak rupee exchange rates. The exchange rate returns and volatility of Pak rupee immediately adjust to most of the foreign and domestic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Similarly, some researchers have successfully-related the behavior of ERV with news announcement. In particular, recently, Jabeen et al (2021) investigated the influence of domestic and foreign macroeconomic news announcement on exchange-rate returns and volatility. They found that both types of news have quite significant role in determining exchange-rate dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, some researchers have successfully-related the behavior of ERV with news announcement. In particular, recently, Jabeen et al (2021) investigated the influence of domestic and foreign macroeconomic news announcement on exchange-rate returns and volatility. They found that both types of news have quite significant role in determining exchange-rate dynamics.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many studies have focused on certain global factors, such as crude oil prices, to determine their impact on the stock market (Al‐hajj, Al‐Mulali, & Solarin, 2021; Gajurel & Chawla, 2022; Xu, Ma, Chen, & Zhang, 2019). Others concentrate on exchange rates (Aquino, 2005; Iyke & Ho, 2021; Jabeen, Rashid, & Ihsan, 2022) or other macroeconomic variables. However, only a few studies have combined more than one macroeconomic variable.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2) We apply “bilateral trade news” as an intermediary, which captures the fluctuations in the China–US economic and trade relationship. Although “news” effects on short‐term exchange rate volatility have been discussed substantially, the majority of the studies have considered macroeconomic news events from only one country and their impact on the related exchange rate (Du & Pentecost, 2021; Korus & Celebi, 2019), or compared the relative influence of macro news from two countries on the bilateral exchange rate (Jabeen et al, 2022). When it comes to the response on the RMB/USD bilateral exchange rate, Chinese and US macroeconomic news were gathered separately (Ho et al, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, the impact of news on bilateral exchange rates has gained increasing attention. Examples of these studies are those on the impact of public information flows on the volatility of the RMB-USD exchange rates (Ho et al, 2017); whether news events measured from big data are significant drivers of unexpected movements in the spot JPY/USD exchange rate (Du & Pentecost, 2021); impact of Brexit-related events on the spot exchange rate of the British pound against the euro and the US dollar (Korus & Celebi, 2019); the effects of the US and PAK domestic macroeconomics on the PKR/USD exchange rates (Jabeen et al, 2022); and the role of economic news in predicting US dollar vis-à-vis the British Sterling Pound exchange rate (Narayan et al, 2021). The majority of these studies have shown significant connections between news events and bilateral exchange rate volatility.…”
Section: Impact Of News Events On Exchange Ratementioning
confidence: 99%